ISOLATION AND STRUCTURE DETERMINATION OF BISDEMTHYLAAPTAMINE FROM BUNAKEN MARINE PARK SPONGE Aaptos, sp. - Wilson AR Rombang; Rymond J Rumampuk; Ponis Tarigan; Anthony J Herlt; Lewis N Mander (Indonesian Journal of Chemistry, 2003)
Bisdemethylaaptamine, an alkaloid naphtyridine with molecular weight 200 and formulae molecule C11H8N2O2 has been isolated from Bunaken Marine Park sponge Aaptos sp. Isolation was done by using several stages of column chromatography and high performance liquid chromatography. Molecular weight of this naphtyridine alkaloid was determined by electron ionization (EI) and electrospray ionization (ESI) mass spectroscopies and its structure assigned to be 8,9-dihydroxy-1H-benzo[d,e][1,6]naphtyridine by proton and carbon nuclear magnetic resonances (1H and 13C-NMR).